New microbombyliids (Diptera: Mythicomyiidae) from Eocene Baltic and Rovno ambers, with notes on previously described amber species - Evenhuis, Neal L. (Zootaxa, 2013)
New mythicomyiids from Baltic and Rovno amber are described and illustrated herein including one new genus: Riga, n. gen.; and five new species: Glabellula aggregata Evenhuis, n. sp., Glabellula perkovskyi Evenhuis, n. sp., Riga toni Evenhuis, n. sp., Carmenelectra shehuggme Evenhuis, n. sp. and Carmenelectra pernigra Evenhuis, n. sp. The genus Riga is very closely related to the extant genus Reissa, which is known from a single species in the Canary Islands. A key to the seven Tertiary species of Glabellula is given. Notes are given clarifying the synonymy of Glabellula; and acting as First Reviser, Mythicomyia dominicana Evenhuis is selected as a correct original spelling. With the description of the new species in this study, the Tertiary fauna of Mythicomyiidae is now 17 species in 8 genera known from Baltic, Saxon, Bitterfeld, French, Rovno (all Eocene), and Dominican (Miocene) ambers.